The Influence of Services on Patient Satisfaction Inpatient BPJS Mitra Sehat Tanjung Morawa General Hospital - Br Sihaloho, Nadia; Octavia, Dina (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
This study aims to determine the effect of service on inpatient satisfaction at Mitra Sehat Tanjung Morawa General Hospital. Data collection techniques were carried out through observation, questionnaires, interviews. The research method used by the author is a quantitative descriptive method. This research was conducted in the city of Medan, Tanjung Morawa. There is also a population of 1149 and the sample used by the author is 100 patients as a test. This disclosure with the result that the Influence of Services on Inpatient Satisfaction in Mitra Sehat Tanjung Morawa General Hospital partially affects inpatient satisfaction